(NaKUSTOPLAZMA (B:s (NmONOGRAFIQ (B/s - d; d; (NnADVARQN(B, (Ng(B.(Nn(B.s; (NiNSTITUT PRIKLADNYH PROBLEM FIZIKI nACIONALXNOJ aKADEMII nAUK rESPUBLIKI aRMENIIs ((NeREWAN (B:s (Nb(B. (NI(B.,s, 2005)
(NrEZ@ME(B: (NANGL(B.s
(NaWT(B. (NIZD(B.s
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NfIZIKA PLAZMYs; (NaKUSTOPLAZMAs